2015
DOI: 10.1111/pin.12314
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bladder urothelial carcinoma with concurrent plasmacytoid and micropapillary differentiations: A report of two cases with an emphasis on serum carbohydrate antigen 19‐9

Abstract: We report two cases of urinary bladder urothelial carcinoma (UC). In both, histological examination of a transurethral resection specimen of the bladder tumor revealed UC with plasmacytoid and micropapillary differentiations. In Case 1, residual plasmacytoid UC deeply invaded the extravesical fat tissue of the radical cystectomy specimen, and metastatic carcinoma was found in almost all the dissected lymph nodes. Despite adjuvant chemotherapy and radiotherapy, the patient died 25 months postdiagnosis. Elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…CD138 is known to be a marker for plasma cells, and variable expression of CD138 in plasmacytoid urothelial carcinoma has been reported in previous studies [ 5 , 6 , 10 , 25 ]. CD138 is also expressed in urothelial carcinoma in situ , conventional urothelial carcinoma, and even normal urothelium [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…CD138 is known to be a marker for plasma cells, and variable expression of CD138 in plasmacytoid urothelial carcinoma has been reported in previous studies [ 5 , 6 , 10 , 25 ]. CD138 is also expressed in urothelial carcinoma in situ , conventional urothelial carcinoma, and even normal urothelium [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 87%
“…Little is known about the HER2 status in plasmacytoid urothelial carcinoma. Only one case report showed HER2 protein expression by IHC in two plasmacytoid urothelial carcinoma cases, of which one case was HER2 IHC 3+ and the other one 2+ [ 25 ]. There has been no study about HER2 gene amplification in plasmacytoid urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mutations that are common in UC were also described in PUC [ 7 , 8 ]. In terms of tumor markers, few reports showed that PUC could produce carbohydrate antigen (CA) 19-9 [ 9 , 10 ]. Herein, we report a patient with CDH-1 mutated PUC who presented with disseminated peritoneal metastasis and had high levels of CA 19-9.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, HER2 was overexpressed in both lipid cell and micropapillary variants of UC compared to most regions of conventional UC, where HER2 expression was weak and incomplete. Micropapillary UC is characterized at the molecular level by frequent overexpression, gene amplification, and/or somatic mutation of HER2 [ 12 , 13 , 14 , 15 ]. De Giorgi et al [ 9 ] have also reported on a case involving HER2 overexpression in the lipid cell variant of UC.…”
Section: Discussionmentioning
confidence: 99%